Dual Periodicity and Molecular Evidence of Brugia Malayi Transmission Dynamics in Banyuasin District, South Sumatra, Indonesia - Rini Pratiwi; Peni Kusumasari; Fitriyanti Fitriyanti; Widyastuti Widyastuti; Alfarobi Alfarobi (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Lymphatic filariasis remains one of the most neglected tropical diseases, characterized by complex transmission dynamics involving parasites, vectors, hosts, and environmental determinants. Understanding the periodicity of Brugia malayi and the molecular confirmation of potential vectors are crucial for optimizing control and elimination strategies in endemic regions. Objective: This study aimed to characterize the transmission dynamics of Brugia malayi by analyzing its microfilarial periodicity and confirming vector species through molecular identification. Methods: A cross-sectional field study was conducted from April 2017 to May 2018 in Banyuasin District, South Sumatra. Peripheral blood samples from humans and domestic cats, as well as adult mosquitoes, were collected and examined microscopically for microfilariae. Polymerase chain reaction (PCR) targeting the yACA gene of Brugia spp. was used for molecular confirmation. Microfilarial periodicity was assessed through hourly finger-prick sampling over 24 hours and analyzed using the Aikat and Das formula. Results: Two of six human subjects in Sedang Village were positive for Brugia malayi microfilariae with an average density of 150.3 mf/mL, while one cat from Muara Sugih was positive for Dirofilaria repens. PCR detected Brugia malayi DNA in two Mansonia spp. samples (I4 and I8) with 93–95% identity to reference strain MG030487.1. The periodicity exhibited a dual pattern diurnal (peak at 15:00) and subperiodic nocturnal distinct from the typical nocturnal rhythm reported elsewhere in Indonesia. Conclusion: The detection of dual periodicity and molecular confirmation of Brugia malayi in Mansonia spp. highlight potential adaptive transmission patterns influenced by local ecological conditions in Banyuasin’s wetland ecosystems.